Exploring wildlife diversity at Noakhali Science and Technology University (NSTU) campus, Bangladesh (Bangladesh Journal of Zoology, 2025)
The study was aimed to assess the wildlife diversity at the Noakhali Science and Technology University (NSTU) campus between November 2023 and October 2024. Data were collected through direct field observations using the line-transect method, plot counting, and interviews with local people. A total of 131 species were identified, representing 24 orders and 69 families. Among these, 5 species (3.82%) were amphibians, 16 species (12.21%) reptiles, 97 species (74.05%) birds, and 13 species (9.92%) mammals. Species richness was highest in tree habitats (53 species, 25.60%), while the winter season was recorded with the highest occurrence (102 species, 35.92%). Among the recorded species, 39 (29.77%) were categorized as very common, 14 (10.69%) as common, 22 (16.79%) as fairly common, and 56 (42.75%) as few. Duttaphrynus melanostictus was found as the most abundant amphibian (49.06%), Calotes versicolor among reptiles (28.74%), Passer domesticus among bird species (10.81%), and Canis aureus was the abundant mammal (27.03%). According to diversity indices, birds exhibited the highest diversity with a Shannon-Wiener index (H = 3.39) and Simpson's diversity index (Ds = 0.95). Of the 97 bird species, 83 (85.57%) were resident and 14 (14.43%) were migratory. Conversely, amphibians showed the highest evenness (E = 0.60).  The findings suggest the need for long-term systematic monitoring and a comprehensive conservation strategy to conserve the wildlife diversity of the study region.Bangladesh J. Zool. 53(1): 111-123, 2025